Implementasi prinsip akuntabilitas dalam manajemen wakaf produktif: studi kasus rumah sakit Islam kota Magelang - Nurodin Usman (State Institute of Islamic Studies (IAIN) Salatiga, 2016)
This study describes the implementation of the principle of accountability in the management ofproductive waqf in the form of Islamic Hospital in Magelang City. The results showed that IslamicHospital is a core business managed by waqf institutions and has experienced significant developmentswith a marked number of users is increasing. The principle of accountability on the Rumah Sakit Islam(Islamic Hospital) Kota Magelang implemented by the Board of Supervisors to supervise routinelybased on a report prepared by the Director of RSI. Implementation of this principle on endowmentsinstitutions is expected to increase the confidence of stakeholders. For the future, supervision throughan external audit needs to be programmed to improve accountability and public trust.